SISTEM UJI KELAYAKAN PENERIMA BLT BPJS MENGGUNAKAN METODE KLASIFIKASI ALGORITMA NAIVE BAYES - Anita Rusmana Lefya; Mustikasari Mustikasari (AGENTS: Journal of Artificial Intelligence and Data Science, 2023)
The large number of registrants who receive Cash Direct Assistance for the Social Security Administering Body (BLT BPJS) in the village of Tamatto, Ujung Loe sub-district, Bulukumba district, makes village staff as managers take a long time to get a decision in the form of whether or not someone is eligible to get assistance. A system of due diligence for beneficiaries of BLT BPJS assistance is needed that can assist village staff. The purpose of this study is to design a system to determine the results of the decisions of recipients who are eligible for BLT BPJS assistance. The type of research carried out is quantitative research with an experimental research approach, the method of data collection is observation. The method used is the nave Bayes algorithm classification method. The results of this study indicate that the eligibility test system for BLT BPJS assistance recipients using the nave Bayes algorithm classification method can help to convey information in the form of the eligibility of a BPJS BLT aid recipient with an accuracy of 83.689% results using as many as 1036 data samples.